Biological effects of allergen–nanoparticle conjugates: uptake and immune effects determined on hAELVi cells under submerged vs. air–liquid interface conditions. Issue 7 (1st June 2020) - Mills-Goodlet, Robert; Schenck, Milena; Chary, Aline; Geppert, Mark; Serchi, Tommaso; Hofer, Sabine; Hofstätter, Nobert; Feinle, Andrea; Hüsing, Nicola; Gutleb, Arno C.; Himly, Martin; Duschl, Albert
Abstract : An allergen–nanoparticle interaction study was performed using hAELVi cells grown under submerged vs. air–liquid interface culture conditions. Choice of cellular models showed impact on the investigation of uptake kinetics and inflammatory responses. Abstract : Type I hypersensitivity reactions against environmental entities, i.e. allergens, are an ever growing problem, with increasing numbers of affected individuals in Western countries. In parallel, nanotechnology has been growing during the past decades, entering more and more areas of application in everyday life. Exposure to allergens may occur in a combined way with environmental particulate matter or (nano-)particles potentially abundant at the workplace. Such combinations may thus affect workers and consumers alike. The present study conceived a methodological and mechanistic approach based on recombinant allergen–SiO2 nanoparticle conjugates and the novel hAELVi cell line as two well-defined model systems to investigate the effects of co-exposure towards allergens and nanoparticles. We applied pristine nanoparticles, allergen–nanoparticle conjugates and unbound allergen under submerged and air–liquid interface conditions. The uptake kinetics and mechanisms, cellular localization and resulting immune responses were studied in hAELVi cells, a cell line derived from human alveolar epithelium showing the characteristics of type I epithelial cells. Modification in the uptake kinetics as well as an increase in pro-inflammatory cyto-/chemokine expression was observed under submerged conditions, but much less under air–liquid interface conditions. While for mechanistic investigations the submerged culture system still proved suitable, more robust and cost-effective, these culture conditions showed considerable deviations in cellular susceptibility observed under more realistic conditions.